\(\dfrac{6^3+3\times6^3+3^3}{13}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
63+3x62+33/13
=63+31x62+33/13
=62x31x(6+32)/13
=1620/13
Em nghĩ là thế !
![](https://rs.olm.vn/images/avt/0.png?1311)
= (2.3)^3+ 3. ( 2.3)^2 + 3^3 / -13
= 2^3 .3^3 + 3. 3^2 . 2^2 + 3^3 / -13
= 3^3. ( 2^3 + 2^2 + 1) /-13
= 27.13/-13
= -27
\(\frac{6^3+3\cdot6^2+3^3}{-13}=\frac{6^2\left(6+3\right)+3^2\cdot3}{-13}=\frac{36\cdot9+9\cdot3}{-13}=\frac{39\cdot9}{-13}=-3\cdot9=-27\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(4\times\left(-\dfrac{1}{2}\right)^3-2\times\left(-\dfrac{1}{2}\right)^2+3\times\left(-\dfrac{1}{2}\right)+1\)
\(=\left(-\dfrac{1}{2}\right)\left[\left(4\times-\dfrac{1}{2}\right)-\left(2\times-\dfrac{1}{2}\right)+3\right]+1\)
\(=\left(-\dfrac{1}{2}\right)\left(-2+1+3\right)+1\)
\(=\left(-\dfrac{1}{2}\right)2+1\)
\(=-1+1\)
\(=0\)
@Trịnh Thị Thảo Nhi
a, 4×(−12)3−2×(−12)2+3×(−12)+14×(−12)3−2×(−12)2+3×(−12)+1
=(−12)[(4×−12)−(2×−12)+3]+1=(−12)[(4×−12)−(2×−12)+3]+1
=(−12)(−2+1+3)+1=(−12)(−2+1+3)+1
=(−12)2+1=(−12)2+1
=−1+1=−1+1
=0=0
![](https://rs.olm.vn/images/avt/0.png?1311)
A =\(\dfrac{4^2}{3\times5}\) \(\times\)\(\dfrac{5^2}{4\times6}\) \(\times\) \(\dfrac{6^2}{5\times7}\) \(\times\) \(\dfrac{7^2}{6\times8}\)
A = \(\dfrac{4\times4\times5^2\times6^2\times7\times7}{3\times4\times5^2\times6^2\times7\times8}\)
A = \(\dfrac{4}{3}\) \(\times\) \(\dfrac{7}{8}\)
A = \(\dfrac{7}{6}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
bài 1
a)\(=\dfrac{16}{40}+\dfrac{15}{40}=\dfrac{31}{40}\)
b)\(=\dfrac{7}{6}-\dfrac{4}{6}=\dfrac{3}{6}=\dfrac{1}{2}\)
c)\(=\dfrac{30}{9}=\dfrac{10}{3}\)
d)\(=\dfrac{8}{5}\times\dfrac{7}{4}=\dfrac{56}{20}=\dfrac{14}{5}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(\dfrac{20^5.5^{10}}{100^5}=\dfrac{20^5.5^{10}}{\left(20.5\right)^5}=\dfrac{20^5.5^{10}}{20^5.5^5}=5^5\)
b,\(\dfrac{\left(0,9\right)^5}{\left(0,3\right)^6}=\dfrac{\left(0,3.3\right)^5}{\left(0,3\right)^6}=\dfrac{\left(0,3\right)^5.3^5}{\left(0,3\right)^6}=\dfrac{3^5}{\left(0,3\right)}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
B1 :
a) \(\dfrac{2}{15}+3=\dfrac{2}{15}+\dfrac{15}{5}=\dfrac{17}{5}\)
b) \(2-\dfrac{7}{4}=\dfrac{8}{4}-\dfrac{7}{4}=\dfrac{1}{4}\)
c) \(\dfrac{17}{6}-\dfrac{11}{12}\times6=\dfrac{17}{6}-\dfrac{11}{2}=-\dfrac{8}{3}\)
d) \(\dfrac{14}{17}:7-\dfrac{15}{34}=\dfrac{2}{17}-\dfrac{5}{34}=\dfrac{4}{34}-\dfrac{5}{34}=-\dfrac{1}{34}\)
B3 :
\(x:23=146\)
\(x=146\times23\)
\(x=3358\)
b) \(x\times38=4066\)
\(x=4066:38\)
\(x=107\)
c) \(787+x\times67=2658\)
\(x\times67=2658-787\)
\(x\times67=1871\)
\(x=1871:67\)
\(x=\dfrac{1871}{67}\)
Ta có : \(\dfrac{6^3+3.6^3+3^3}{13}=\dfrac{6^3.\left(1+3\right)+3^3}{13}=\dfrac{6^3.4+3^3}{13}\)
=> \(\dfrac{\left(3.2\right)^3.4+3^3}{13}=\dfrac{3^3.2^3.4+3^3}{13}=\dfrac{3^3.2^5+3^3}{13}\)
=> \(\dfrac{3^3.\left(2^5+1\right)}{13}=\dfrac{3^3.33}{13}=\dfrac{891}{13}\)
\(\dfrac{6^3+3\times6^3+3^3}{13}\)
= \(\dfrac{216+648+27}{13}\)
= \(\dfrac{891}{13}\)
@Trịnh Thị Thảo Nhi